High leptin levels are associated with migraine with aura. (April 2017) - Pisanu, Claudia; Preisig, Martin; Castelao, Enrique; Glaus, Jennifer; Cunningham, Janet L; Del Zompo, Maria; Merikangas, Kathleen R; Schiöth, Helgi B; Mwinyi, Jessica
Background: Migraine is a prevalent disorder characterised by recurrent headache attacks preceded or accompanied by aura in a subgroup of patients. Migraine often occurs together with major depressive disorder (MDD). Alterations of adipokine levels have been reported both in migraine and in MDD. In this cross-sectional study, we aimed to assess the associations between serum leptin and adiponectin levels and migraine or migraine subtypes. Analyses were adjusted for a lifetime history of MDD in order to investigate the association between adipokines and migraine under consideration of depression status. Methods: We included 3025 participants from the CoLaus/PsyCoLaus study. The impact of leptin and adiponectin levels on a diagnosis of migraine was analysed by binary regression analyses, adjusting for variables known to influence adipokine levels. Subgroup analyses were conducted based on the presence of aura. Results: Crude leptin levels were significantly higher in subjects with migraine than controls (Mann–Whitney U = 515, 102, p = 6 × 10 −7 ). When performing adjusted analyses, leptin levels were found to be significantly higher in subjects with migraine (odds ratio = 1.22, p = 0.024) and migraine with aura (odds ratio = 1.34, p = 0.004). Conclusion: High leptin levels might play a role in the pathogenesis of migraine and migraine with aura.